Short and Long-Term Effects of Anesthesia in Octopus maya (Cephalopoda, Octopodidae) Juveniles - Roumbedakis, Katina; Alexandre, Marina N.; Puch, José A.; Martins, Maurício L.; Pascual, Cristina; Rosas, Carlos (Frontiers in Physiology, 2020)
This study aimed to explore different substances (or cold sea water) as potential anesthetic agents to facilitate short-term handling in Octopus maya juveniles. We investigated oxygen consumption before (baseline), during (first 600 s of exposure) and after anesthesia (recovery) of octopuses (n = 98; 1.67 ± 0.5 g) exposed to cold sea water (SW; 11 and 13°C), ethanol (EtOH; 0.5; 1.5 and 3.0%), magnesium chloride (MgCl2; 0.75; 1.5 and 3.75%), ethanol combined with magnesium chloride (Mix; 1.5:0.75%; 0.75:1.13%; and 2.25:0.37%) and clove oil (0.15 mL L–1). After exposure, the animals were handled for 180 s (exposed to air) and weighted. Two experimental groups not exposed to anesthetics (with or without handling) were also evaluated. The criteria for general anesthesia were analysed. Times of induction and recovery, incidence of attack response after recovery and possible longer-term effects of repeated general anesthesia on growth and mortality of the octopuses were evaluated. During anesthesia, O. maya juveniles exposed to SW (11 and 13°C), EtOH (0.5; 1.5 and 3.0%), Mix (0.75:1.13%), and clove oil, presented a significant decrease on oxygen consumption. In animals exposed to different concentrations of EtOH and Mix 0.75:1.13%, this decrease was registered after an increase on oxygen consumption. Animals exposed to MgCl2 did not show significant changes on oxygen consumption, except for animals exposed MgCl2 3.75%, which showed a significant increase on oxygen consumption. At the end of recovery, except for octopuses exposed to clove oil and MgCl2 0.75%, the values of oxygen consumption observed were comparable to the ones registered during baseline. Animals exposed to SW 11°C, EtOH 3.0%, Mix 1.5:0.75% and MgCl2 3.75% fulfilled the criteria defined for general anesthesia. Exposure to MgCl2 (all concentrations), SW 13°C and clove oil reduced or inhibited the incidence of attack response after recovery. Except for animals exposed to clove oil, growth of the juveniles was not affected by the exposure to the different substances. Short-term handling (180 s) of O. maya juveniles can eventually be carried out without anesthesia. However, to facilitated handling, we suggest the use of EtOH 3.0% or cold sea water 11°C.